Urban water supply through private tanker water markets: An empirical market analysis of Amman, Jordan - Katja Sigel; Christian Klassert; Heinrich Zozmann; Samer Talozi; Bernd Klauer; Erik Gawel (Helmholtz-Zentrum für Umweltforschung (UFZ), 2017)
The Hashemite Kingdom of Jordan faces a severe water crisis. The Ministry of Water and Irrigation (MWI) in Jordan estimated the annual per capita share of water for domestic uses at 147 cubic meters in 2010 and 126 cubic meters in 2015 indicating a continuous decline in the ability of Jordan's water sector to provide water for the growing population; while, and for the same years, the annual groundwater uses for all purposes increased from 511 million cubic meters (MCM) to nearly 602 MCM indicating an increased reliance on groundwater to meet increasing demands.1 According to the above mentioned indicators, Jordan is on the list of the ten countries with the least availability of water resources. Strong population growth and influx of refugees, climate change and unsustainable practices in water management are likely going to exacerbate current conditions (AFD 2011). One of the central challenges of water governance in Jordan is the ongoing overexploitation of its groundwater resources (Kubursi et al. 2011). While the safe yield of groundwater pumping is estimated at 418.5 MCM in 2015, abstractions surpassed this level by 205.8 MCM in 2015.2 Another pivotal challenge of water management in Jordan remains the so-called nonrevenue water (NRW). NRW denotes water that enters the networks at the input level but remains unmetered at the output level, which is either due to technical (e.g., leaks) or administrative losses (e.g., surpassed meters). In 2016, the Jordanian Ministry of Water and Irrigation (MWI) reported that, on average, 126 liters of water were pumped into countrywide supply systems per person and day (MWI 2016b). Yet, only 61 liters reached the water users, while the remaining 65 liters, i.e. 52 %, got lost during conveyance. The low availability of water in combination with the high losses during transport has led to a pervasive gap between publicly supplied water volumes and the demands of residential and non-residential consumers. As a result, water shortages and supply intermittency occur throughout the country (WAJ 2015). (...)
urn:nbn:de:gbv:3:2-141140
Keywords: 330